Presence of E. coli O157:H7 in Cakes Marketed in Elazı? - Öksüztepe, Gülsüm; Patir, Bahri; Çalicio?lu, Mehmet; Ilhak, O. Irfan; Dikici, Abdullah (Veteriner Fakultesi Dergisi, 2010)
The present study was undertaken to investigate the presence of Escherichia coli O157:H7 in cakes (plain, with cacao, with fruit) marketed in Elazi{dotless}?. A total of 200 cake samples as 100 plain, 50 with cacao, and 50 with fruit were analysed. Following the enrichment, the samples were plated on to CT-SMAC agar. A total of 208 typical colonies (colourless) as 138 colonies from 65 plain cakes, 25 colonies from 8 cakes with cacao, and 45 colonies from 19 cakes with fruit were isolated. These colonies were subjected to further analysis given in the materials and methods section for identification of serotype O157:H7 of E. coli. However, no colonies representing E. coli O157 were detected in any of the samples. Therefore, analysis was not proceeded for determining H7 in any of the isolates. E. coli O157:H7 was not detected in any of the cake samples analyzed. Although this finding is a good news for public health, considering other pathogens, which may exist in cakes, it is concluded and reemphasized that strict hygienic practices should be applied at every stage of cake production.
Elazı?'da satılan Kremalı pastalarda e. coli o157:H7'nin varlı?ı
Keywords: Cake; E. coli 0157:H7; Microbiolgy; Public health; Quality